2022
DOI: 10.1002/marc.202200293
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfined Crystallization in Poly(lactic acid) (PLA) and Poly(ethylene terephthalate) (PET) Induced by Various Forms of Premelt‐Deformation

Abstract: The processing–structure–property relationship using poly(lactic acid) (PLA) and poly(ethylene terephthalate) (PET) is explored. Specifically, both pre‐extension and preshear of amorphous PLA and PET above their glass transition temperatures Tg, carried out in the affine deformation limit, can induce a specific type of cold crystallization during annealing, i.e., nanoconfined crystallization (NCC) where crystal sizes are limited to a nanoscopic scale in all dimensions so as to render the processed PLA and PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…However, polylactic acid has disadvantages, including hydrophobicity, brittleness at room temperature, low thermal resistance, slow degradation rate, permeability to gases, lack of active groups, and chemical neutrality. 4–10…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, polylactic acid has disadvantages, including hydrophobicity, brittleness at room temperature, low thermal resistance, slow degradation rate, permeability to gases, lack of active groups, and chemical neutrality. 4–10…”
Section: Introductionmentioning
confidence: 99%
“…However, polylactic acid has disadvantages, including hydrophobicity, brittleness at room temperature, low thermal resistance, slow degradation rate, permeability to gases, lack of active groups, and chemical neutrality. [4][5][6][7][8][9][10] Applications of PLA include medical use for sutures and surgical implants. [10][11][12][13][14][15] Joints of surgical implants, such as pins and tubes, are also made of PLA, which breaks down in the human body within six months to two years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoconfined crystallization was thus achieved 306 . Finally, acetone vapor is also reported to induce PLA crystallization by diffusion into the material 307 .…”
Section: Treatmentsmentioning
confidence: 99%
“…This is also consistent for other deformation techniques such as pressure induced fluidization of the material with T400-800 >80 % 305 . It is furthermore shown that pre-extension and pre-shear can influence the formation of PLA crystallites during annealing 306 .…”
Section: Treatmentsmentioning
confidence: 99%